Israeli Protests in Instagram Posts of International News Agencies - Kılıç, Ekmel; Uğuş, Mikail (Fırat University, 2025)
International news agencies such as Reuters, Agence France Presse (AFP), and Associated Press (AP) dominate the global flow of information. A large portion of the news presented in newspapers, on radio, and on television originates from these three agencies. To connect directly with the end consumer, smaller and less-known agencies have leveraged websites and social media platforms, enabled by advancements in internet and communication technologies. This shift is significant, as news agencies often reflect the political and economic interests of their home countries. Consequently, nations seeking to shape international public opinion have established their own news agencies, using them as tools of public diplomacy. This study examines Instagram posts by international news agencies regarding Israeli protests initiated by pro-Palestinian university students in the U.S. that later spread to Europe. Findings revealed that Reuters, AP, and AFP portrayed the protests negatively and with bias, while Anadolu Agency reported them positively, aligning with Türkiye's political stance on the Palestinian issue. This highlights the influence of national interests on news coverage.

Uluslararası haber ajansları olan Reuters, Agence France Presse (AFP) ve Associated Press (AP) dünyadaki haber akışını önemli ölçüde kontrol etmektedir. Gazete, radyo ve televizyonda farklı kanal ve isimlerde yayınlanan haberlerin önemli bir bölümü bu üç ajanstan gelmektedir. Bu nedenle son tüketici tarafından pek bilinmeyen haber ajansları internet ve bilgi teknolojilerinin gelişim göstermesiyle beraber kendi internet sitelerini ve sosyal medya hesaplarını oluşturmuşlardır. Bu sayede son tüketiciye doğrudan ulaşmaya başlamışlardır. Haber ajanslarının faaliyetleri bağlı oldukları ülkelerin siyasi ve ekonomik çıkarlarından bağımsız olmadığı için son tüketiciye ulaşma çabaları da anlamsız değildir. Uluslararası kamuoyunu etkilemek isteyen diğer ülkeler de kendi haber ajanslarını kurmuşlardır. Ülkeler, kamu diplomasisi aracı olarak haber ajanslarını kullanmaktadırlar. Çalışma kapsamında Amerika’da başlayıp tüm Avrupa’ya yayılan Filistin yanlısı üniversite öğrencilerinin düzenledikleri İsrail protestoları ele alınmış ve uluslararası haber ajansları ile Anadolu Ajansı’nın (AA) İsrail protestoları hakkındaki Instagram paylaşımları incelenmiştir. Çalışma sonucunda Reuters, Associated Press ve Agence France Presse’in İsrail protestolarını olumsuz ve yanlı şekilde haberleştirdikleri tespit edilmiştir. Buna karşın, Türkiye’nin Filistin meselesinde gösterdiği siyasi duruşa uygun olarak, Anadolu Ajansı’nın İsrail protestolarını olumlu ve yanlı şekilde haberleştirdiği görülmüştür.
Uluslararası Haber Ajanslarının Instagram Paylaşımlarında İsrail Protestoları
Keywords: Globalisation and Culture; Küreselleşme ve Kültür; Communication Sociology; İletişim Sosyolojisi